Edukasi Makanan dan Jajanan Sehat Serta Bergizi Pada Anak Sekolah Dasar - Dewi Asriani Ridzal; Fajrianti Fajrianti; Haswan Haswan; Veni Rosnawati (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Processed food with an attractive appearance which is often sold by traders in the school environment is a special attraction for students to consume, including at SD Negeri 1 Bandar Batauga.  The large number of cases of health problems such as poisoning due to children consuming food and snacks sold in the area around the school without knowing whether the food is good for consumption or not is the basis for this activity to be carried out.  The service activity aims to educate elementary school-age children about healthy and nutritious food and snacks for consumption in the form of education which consists of four stages, namely observation, implementation of activities (education), evaluation, and reporting of activity results.  This activity took place at SD Negeri 1 Bandar Batauga and was attended by 22 students.  Service activities in the form of education have a positive influence on students' understanding and knowledge about healthy and nutritious food preparations. This is based on the results of activity evaluations which show that 81% of participants are in the good category (understand), 14% are in the sufficient category (somewhat understand) and 5 % are categorized as lacking (lack of understanding).  Overall, service activities run in accordance with the stated objectives.